Women Lead the Municipality: A Contribution on the Metamorphosis of Czechoslovak Society after the Communist Revolution - Nečasová, Denisa (Dějiny – teorie – kritika, 2011)
The study is devoted to the issue of the implementation of the communist visions in Czechoslovak society after the communist revolution on the model of the deliberate placement of women in the leadership of local national committees in small municipalities in 1950. The interest of communist power in a higher number of women active in the national committees arose from the problematic situation of the national committees themselves, which were to form the backbone of the power state apparatus reaching even to the remotest parts of the republic. Along with that, there was also an attempt to include women much more actively than before in the socialist building enthusiasm. The author examines in detail both the agitation campaign aimed at women and the gender stereotypes, which were applied when viewing women and members or even presidents of the national committees.